Perancangan Sistem Karir Berbasis Web Menggunakan Framework Laravel - abdul khaliq (CV. Hawari, 2023)
Advances in data and communication technology are growing rapidly. Especially in terms of data, data plays an important role in life. In this modern era, data is carried by a technology called the internet. In this case, the internet makes it easy to provide data about job vacancies, one of which is job vacancy websites. Without data it will be very difficult to get something you want, like getting a job. Profession is a matter that is very important for the survival of some people, therefore many people have difficulty getting data on a profession, but there are also people who have an industry who also have difficulty getting employees quickly and with the skills that match the required aspects. To overcome this problem, a website-based job vacancy application arrangement was created called a web search program, using the waterfall method, made using the PHP programming language and MySQL as the database. With this application, it is hoped that it will make it easier for applicants to find data on professional vacancies and make it easier for an industry that is looking for employees quickly and with the right skills